NURSES’ COMPLIANCE ON PATIENT HANDOVER PROCESS IN THE PRE-OPERATIVE ROOM OF THE HOSPITAL IN VIETNAM - Nhut Minh Nguyen; Xuan Thi Nhu Ha; Katrina Einhellig (Belitung Raya Foundation, Indonesia, 2020)
Background: Ineffective handover is considered a major factor that endangers patient safety in hospitals. Preparing and handing over patients before surgeries directly impact the outcome of the surgery. If errors occur, they could jeopardize the patient’s life. Objectives: To determine the level of nurses’ compliance during the pre-operative patient handover process at the anesthesia department. To examine nurses’ evaluation on using a pre-operative patient handover checklist. Methods: This was a descriptive observational study with a cross-sectional approach to examine 196 cases of handing over pre-operative patients performed by 53 nurses from the surgical department, maternity department, obstetrics and gynecology department, emergency department, and anesthesia department. Data were collected from November 2019 to February 2020 using “The Checklist of Assessing Nurse’s Compliance on Pre-Operative Patient Handover” and “The Survey Form of Nurse’s Evaluation on Using Pre-Operative Patient Handover Checklist.” Descriptive statistics, including frequencies and percentages, were used for data analysis. Results: Nurses’ compliance on handing over pre-operative patients with a high level was 71.9%, and with an average level was 28.1%. The handover areas with low compliance rate included: the patients need to be isolated (63.3%), identifying patient information verbally (75%), identifying patient information by hospital bracelet (77%), time to use antibiotics (78.1%), and marked surgical site (79.6%). Over 90% of nurses agreed on the usefulness of the pre-operative handover checklist. Conclusion: The process of handing over pre-operative patients was performed relatively well, but there were still shortcomings to overcome. Nurses positively evaluated the use of the handover checklist for preparing pre-operative patients.